2006
DOI: 10.1002/bdra.20303
|View full text |Cite
|
Sign up to set email alerts
|

Risks of hyperthermia associated with hot tub or spa use by pregnant women

Abstract: There are a limited number of human studies linking hot tub or spa use during early pregnancy to increased risks for neural tube defects (NTDs) or spontaneous abortion. However, these data can be considered in the context of human studies that have demonstrated an association between high maternal fever in early pregnancy and NTDs. In addition, there is a large volume of animal literature suggesting that, regardless of the heat source, an elevated core maternal temperature at or above the threshold of 2 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…Among these congenital malformations, NTDs have the highest frequency (Edwards, 2006). The effect of hyperthermia on neural development is closely related to the stage of pregnancy and the duration and amplitude of the temperature increase (Chambers, 2006). Clinical investigation showed that the incidence of NTDs would increase greatly if the temperature exceeded 38.98C during early pregnancy and become even higher if the temperature exceeded 408C (Moretti et al, 2005;Chambers, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these congenital malformations, NTDs have the highest frequency (Edwards, 2006). The effect of hyperthermia on neural development is closely related to the stage of pregnancy and the duration and amplitude of the temperature increase (Chambers, 2006). Clinical investigation showed that the incidence of NTDs would increase greatly if the temperature exceeded 38.98C during early pregnancy and become even higher if the temperature exceeded 408C (Moretti et al, 2005;Chambers, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of hyperthermia on neural development is closely related to the stage of pregnancy and the duration and amplitude of the temperature increase (Chambers, 2006). Clinical investigation showed that the incidence of NTDs would increase greatly if the temperature exceeded 38.98C during early pregnancy and become even higher if the temperature exceeded 408C (Moretti et al, 2005;Chambers, 2006). In this study, we adopted the model of hyperthermia as established in a previous study, in which hyperthermia could induce the NTDs with a rate up to 80% (Feng, et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…If the tympanic temperature was found to be > 1.5 8C above the resting temperature (the safe upper limit for maternal core temperature rise reported in the pregnancy literature [13][14][15] ), or if the participant looked flushed or felt uncomfortably warm or hot, she was asked to cease exercising.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Among human studies the teratogenic effect of hot tub and sauna bathing related hyperthermia (Chambers, 2006) are not shown here, only the possible association of high fever related maternal diseases with CAs mentioned in Table 19.1 is discussed here, although the teratogenic effect of hyperthermia was proved to have a role in the origin of other CAs as well such as microphthalmia (Fraser and Skelton, 1978), facial defects like micrognathia, midfacial hypoplasia, external ear CA, micropenis (due to LH deficiency), and neurogenic contractures Jones, 2004). However, we know a limited number of human studies which were unable to find an association between hyperthermia and CAs (Kleinbrecht et al, 1979;Chambers et al, 1998).…”
Section: High Fever Related Maternal Diseases During Pregnancy 437mentioning
confidence: 99%